USING VIRTUAL REALITY (VR) TECHNOLOGY AS AN EFFORTS TO ESCALATE INTEREST IN ONLINE LEARNING DURING PANDEMIC - Ariatama, Soni; Adha, Muhammad Mona; Rohman, Rohman; Hartino, Ahman Tosy; Ulpa, Eska Prawisudawati (Universitas Lampung, 2021)
Achieving this goal, humans continue to innovate in making assistive devices to carry out teaching and learning activities, where one of them is making a learning medium. The pandemic period that occurred in 2020 made learning carried out online so that online learning platforms or media became very important to mastered and implemented by both teachers and students. Learning media using virtual reality (VR) is an alternative solution to offer new and fun learning practices for students. VR brings interesting videos/images with adjustable time duration. This article uses a literature study approach, by collecting various materials and information, then the analysis made based on the documentation and reflections that have been compiled. The use of VR encourages learning media innovations that are different from before to increase participation and students' critical thinking perspectives and to bring students closer to VR technology. The characteristics of technology that are suitable for use such as Virtual Reality (VR) media can be implemented in the teaching and learning process in the midst of the current pandemic which aims to attract students' interest and feel a classroom-like atmosphere when offline learning takes place.Keywords: online learning, pandemic, technology, virtual reality DOI: http://dx.doi.org/10.23960/jpvti.v3.i1.202101